TREND BLENDED LEARNING PADA PEMBELAJARAN DI NEW NORMAL DARI PANDEMI COVID-19 - Rita Hidayahwati (JOEL: Journal of Educational and Language Research, 2021)
The goal of this research is to explain the role of blended learning methodologies in the Covid-19 pandemic's "New Normal" era. Blended learning is one of the training strategies that mixes online and offline learning to prevent mass gathering activities as one of the health treatments to avoid Covid-19. Blended learning is a learning approach or method that focuses on improving knowledge, abilities, and attitudes in order to achieve the desired learning objectives. In learning mathematics, the blended learning technique combines three elements into a single learning experience. These elements are: 1) online learning, 2) face-to-face learning, and 3) self-study. In light of the advancement of information and communication technology, the blender learning technique is suited for use in learning mathematics for future learning.